G Company's war : two personal accounts of the campaigns in Europe, 1944-1945 - Egger, Bruce E., 1923-; Otts, Lee MacMillan, 1922-; Roley, Paul, 1927- (Tuscaloosa : University of Alabama Press, 1992)
This unique account of combat in World War II provides parallel day-to-day records of the same events as seen by two men in the same company, one an enlisted man, one an officer. G Company's War is the story of a World War II rifle company in Patton's Third Army as detailed in the journals of S/Sgt. Bruce Egger and Lt. Lee M. Otts, both of G Company, 328th Regiment, 26th infantry Division. Bruce Egger arrived in France in October 1944, and Lee Otts arrived in November. Both fought for G Company through the remainder of the war. Otts was wounded seriou.
Maps; Acknowledgments; Introduction; Prologue; 1. First Blood; 2. The Mud of Lorraine; 3. Transition: From Lorraine to Metz; 4. Into the Bulge; 5. Victory in the Ardennes; 6. The Saarlautern Interlude; 7. The Drive to the Rhine; 8. The Race across Germany; Epilogue; Appendix I: The Reckoning; Appendix II: Roll Call; Notes; Index
Includes bibliographical references (pages 281-286) and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
eBooks on EBSCOhost
Keywords: Egger, Bruce E., -- 1923-; Otts, Lee MacMillan, -- 1922-; United States. -- Army -- Biography; United States. -- Army. -- Infantry Regiment, 328th. -- Company G -- History; États-Unis. -- Army -- Biographies; Egger, Bruce E., -- 1923-; Otts, Lee MacMillan, -- 1922-; United States. -- Army; United States. -- Army. -- Infantry Regiment, 328th. -- Company G; United States. -- Army. -- Infantry Regiment, 328th. -- Company G; World War, 1939-1945 -- Campaigns -- Western Front; World War, 1939-1945 -- Personal narratives, American; Soldiers -- United States -- Biography; Guerre mondiale, 1939-1945 -- Campagnes et batailles -- Front occidental; BIOGRAPHY & AUTOBIOGRAPHY -- Historical; HISTORY -- Military -- World War II; Military campaigns; Soldiers; United States; Western Front (World War (1939-1945)); Soldat; Erlebnisbericht; Europa; USA; World War, 1939-1945 -- Campaigns -- Western Front; World War, 1939-1945 -- Personal narratives, American; Geschichte (1944-1945); 1939 - 1945; World War 2 -- Army operations; Europe; Biography; Personal Narrative; Personal narratives; Biographies; History; Personal narratives -- American; Biographies; Personal narratives; Biographies; Récits personnels